(untitled) (World Bulletin of Public Health, 2024)
Immunohistochemical methods for the study of lung tissue in bronchiectatic disease in experimental animal conditions are necessary for a deeper understanding of the cellular and molecular mechanisms of chronic respiratory diseases and the development of new approaches to their diagnosis and therapy